2019
DOI: 10.3390/ma12040579
|View full text |Cite
|
Sign up to set email alerts
|

Post-Impact Behaviour of Pseudo-Ductile Thin-Ply Angle-Ply Hybrid Composites

Abstract: This work experimentally explores the post-impact behaviour of thin-ply angle-ply pseudo-ductile carbon fibre laminates subjected to tensile load. Indentation and low-speed impact tests were performed on standard tensile test specimens. Non-destructive tests were used to investigate the damage propagation. Digital Image Correlation (DIC) was adopted to detect the strain distribution during tensile tests. Post-damage pseudo-ductile behaviour was retained in angle-ply hybrid composites subjected to tensile loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Pseudo-ductility is the mechanical property of a functional material to possess the ability of brittle (high strength) and ductile material (high value of elongation) at the same time [ 1 ]. According to the most accepted theory, it is possible for a material to undergo pseudo-ductile behaviour if the deformation starts before the yield point in a tensile test [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudo-ductility is the mechanical property of a functional material to possess the ability of brittle (high strength) and ductile material (high value of elongation) at the same time [ 1 ]. According to the most accepted theory, it is possible for a material to undergo pseudo-ductile behaviour if the deformation starts before the yield point in a tensile test [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the outright knowledge of various aspects of tensile testing (a measure of hardness, a measure of onset of viscoelastic deformation, the area under the curve and slope of the stress–strain curve of materials) are of great importance [ 3 ]. Thus, pseudo-ductility is of significant importance because it increases the range of engineering and technical application of a material [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in this study, local stress distribution around the impact indent on the impacted laminate surface was determined under in-plane tensile loading using DIC technique. Prato et al [10] also had measured longitudinal surface strain map on the impacted carbon fiber laminates with DIC technique and locally concentrated strain around the hemispherical indent was measured.…”
Section: Stress Concentration Around the Impact Indentmentioning
confidence: 99%
“…Impact damage strength degradation and progress of the damage were also investigated. Prato et al [10] evaluated the residual pseudo-ductile behavior in tension for carbon fiber laminates, and reported that the damage area increased progressively as the impact and absorbed energy increased, and the full-field longitudinal strain distribution was measured by the DIC (Digital Image Correlation) system. Husman et al [11] analyzed the local impact resistance of the composite laminate with fracture mechanics model as a laminate containing a hole of the same diameter as the impacting diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The following exemplary paper could be mentioned: (i) the influence of impact position on damages have been investigated by Sun and Hallett [17], (ii) the effects of ply clustering on polymer-based laminated composite plates subjected to impact load have been considered by Gonzales et al [18], (iii) the influence of layer arrangement, impact energy, and ball velocity on damage area, strain in time relation, delamination area vs. impact energy in the case of single impact and multiple impacts based on not standard specimen dimensions (i.e., panels 900 mm × 1100 mm) were tested by Nassr et al [19], (iv) the influence of impact energy and impact force on delamination area of GFRP plates with rectangular and circular shape have been investigated by Cantwell [20]. (v) Further, the influence of drop off configuration on impact load response have been analyzed by Abdulhamid et al [21], (vi) Shyr and Pan [22] showed multi-elements analysis of impact resistance of fiber glass composite materials, (vii) the tensile tests on initially pre-damaged thin-ply angle-ply pseudo-ductile carbon fiber laminates have been investigated by Prato et al [23], (viii) Gliszczynski et al [24,25] investigated the low velocity impact damages in plate and channel section profile on size and shape of damage with comparison to standard CAI tests. Additionally, the repaired and non-repaired specimens after impact was tested by Kumari et al [26] in compression test, who investigated their behaviour till damage.…”
Section: Introductionmentioning
confidence: 99%